Status and related factors of medication safety behaviour of nurses in the operating room: A cross-sectional survey in China - Xiuwen Chen; Xueyi Wei; Liqing Yue; Duo Wu; Jiqun He (PLoS ONE, 2025)
Aim This study aimed to investigate the current status and influencing factors of medication safety behaviour of operating room nurses. Background Medication safety is an important safety issue recognised by health organisations all over the world, and the operating room has one of the highest rates of preventable medication-related injuries. However, few studies have investigated the current status and influencing factors of medication safety behaviour of operating room nurses. Design A cross-sectional study. Methods From February to March, this study was conducted at three tertiary hospitals in southern China. Operating room nurses completed a series of questionnaires, including nurses’ medication environment perception scale and operating room nurse’s medication safety behaviour questionnaire. Data analysis included descriptive statistics, ANOVA, correlation analysis, and multiple regression. The STROBE checklist guided the reporting of this study. Results A total of 171 questionnaires were analysed. The total score on medication safety behaviour of operating room nurses was 78.20±8.94. The medication environment the operating room nurses perceived was positively correlated with medication safety behaviour (P < 0.01). Additionally, factors related to the medication safety behaviour of operating room nurses included working years(B = 4.899, P = 0.000), the highest level of education(B = 5.440, P = 0.000), professional title(B = −2.644, P = 0.002), the last time of nursing medication safety training(B = −0.914, P = 0.013), and the system and supervision (B = 0.141, P = 0.015). Conclusion The medication safety behaviour of operating room nurses is low. The relationship between individual factors, medication environment, and medication behaviour of operating room nurses should be deeply considered, and targeted intervention strategies should be carried out to influence factors to improve their medication safety behaviour.